Molecular mechanism of bone metastasis in breast cancer - Sui, Laijian; Wang, Jing; Jiang, Wen G.; Song, Xicheng; Ye, Lin (Frontiers in Oncology, 2024)
Bone metastasis is a debilitating complication that frequently occurs in the advanced stages of breast cancer. However, the underlying molecular and cellular mechanisms of the bone metastasis remain unclear. Here, we elucidate how bone metastasis arises from tumor cells that detach from the primary lesions and infiltrate into the surrounding tissue, as well as how these cells disseminate to distant sites. Specifically, we elaborate how tumor cells preferentially grow within the bone micro-environment and interact with bone cells to facilitate bone destruction, characterized as osteoclastic bone metastasis, as well as new bone matrix deposition, characterized as osteoblastic bone metastasis. We also updated the current understanding of the molecular mechanisms underlying bone metastasis and reasons for relapse in breast cancer, and also opportunities of developing novel diagnostic approaches and treatment.